2005
DOI: 10.2807/esm.10.02.00522-en
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus, hepatitis C and hepatitis B infections among blood donors in Germany 2000-2002: risk of virus transmission and the impact of nucleic acid amplification testing

Abstract: Blood and plasma donations in Germany are collected by several institutions, namely the German Red Cross, community and hospital-based blood services, private blood centres, commercial plasma donation sites and transfusion services of the army. All blood donation centres are required to report quarterly data on infection markers to the Robert Koch Institute, thus providing current and accurate epidemiological data. The prevalence and incidence of relevant viral infections are low in the blood donor population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
56
0
7

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 23 publications
0
56
0
7
Order By: Relevance
“…As the HBsAg and anti-HBc prevalence, the anti-HCV prevalence found in Brazil was higher than in developed countries like United States (0.25% in 2002) ), Germany (0.1% in 1997 (Offergeld et al 2005), Canada (0.017% in 2000) (Chiavetta et al 2003), and Italy (0.002% in 1994/1997) (Tosti et al 2002).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…As the HBsAg and anti-HBc prevalence, the anti-HCV prevalence found in Brazil was higher than in developed countries like United States (0.25% in 2002) ), Germany (0.1% in 1997 (Offergeld et al 2005), Canada (0.017% in 2000) (Chiavetta et al 2003), and Italy (0.002% in 1994/1997) (Tosti et al 2002).…”
Section: Discussionmentioning
confidence: 89%
“…In this study, the overall, 0.27% HBsAg prevalence in volunteer blood donors from Rio de Janeiro, in the period encompassed between 1998-2005, was lower than in Lábrea, state of Amazonas (3.3% in 2000) (Braga et al 2005) and state of Santa Catarina (0.7% in 1994-1995) (Treitinger et al 2000), and in 1999-2001 (0.98, 0.84, and 0.64% respectively) (Rosini et al 2003). However, a comparison with developed countries, like Germany (0.16% in 1997-2002) (Offergeld et al 2005), United States (0.07% in 2002) (Zou et al 2004), Italy (0.003% in 1994-1997) (Tosti et al 2002), and Canada (0.012% in 2000) (Chiavetta et al 2003) showed that HBsAg prevalence estimates in Rio de Janeiro blood donors were higher.…”
Section: Discussionmentioning
confidence: 97%
“…There is evidence, at least from Denmark and the Netherlands, that the number of HBV infections transmitted by sexual contact has recently been increasing [32,33] but injecting drug use is a major mode of transmission in many countries [32,34]. In the past, HBV was frequently transmitted via blood transfusion, but due to improved testing of blood donors the estimated residual risk of acquiring HBV infection ranges from 1 to 10 per million transfusions in Europe [35][36][37][38][39]. The transmission of HBV infection may also occur through needle stick injuries, which is why health care workers can be at higher risk of getting the HBV infection.…”
Section: Transmission Routes and Prevention Of Hbvmentioning
confidence: 99%
“…The implementation of effective virus inactivation procedures and of anti-HCV testing methods in the late 1980s and early 1990s, as well as the recent introduction of HCV RNA tests significantly improved the safety of blood products [44]. The estimated residual risk for acquiring HCV via blood products ranges from 1 to 40 per 10 million transfusions in Europe [35][36][37][38][39].…”
Section: Transmission Routes and Prevention Of Hcvmentioning
confidence: 99%
“…Currently, blood centers in industrialized countries rigorously screen blood donations for known pathogens and have now implemented nucleic acid testing that further reduces HIV transmission before serological conversion (3,38). Unfortunately, these highly sensitive detection tests do not eliminate the period of potential infectivity.…”
mentioning
confidence: 99%